2018
DOI: 10.15388/lmr.a.2018.02
|View full text |Cite
|
Sign up to set email alerts
|

On the associativity property of MPF over M16

Abstract: The objective of this paper is to find suitable non-commuting algebraic structure to be used as a platform structure in the so-called matrix power function (MPF). We think it is non-trivial and interesting problem could be useful for candidate one-way function (OWF) construction with application in cryptography. Since the cornerstone of OWF construction using non-commuting algebraic structures is the satisfiability of certain associativity conditions, we consider one of the possible choices, i.e. the group M16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…In this paper we recall one of the possible non-commuting groups to be used as a platform for MPF. Previous investigation of the properties of the MPF defined over the group M 16 presented in [25] has shown that we can construct cryptographic primitives using this group as a platform. Due to the properties of M 16 presented in that paper, we have to define templates for private session parameters.…”
Section: Our Previous Contributions and Novelty Of This Papermentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper we recall one of the possible non-commuting groups to be used as a platform for MPF. Previous investigation of the properties of the MPF defined over the group M 16 presented in [25] has shown that we can construct cryptographic primitives using this group as a platform. Due to the properties of M 16 presented in that paper, we have to define templates for private session parameters.…”
Section: Our Previous Contributions and Novelty Of This Papermentioning
confidence: 99%
“…Nevertheless, we can use some facts from our previous research to establish a working key exchange protocol between Alice and Bob. To achieve this goal, we have previously considered the basic properties of the MPF defined over M 16 in [25]. Relying on the obtained conclusions and a specified form of the base matrix W we defined several possible templates for power matrices mainly focusing on the left side of (8).…”
Section: Description Of Mpf and Its Basic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, we consider a general form of one of the previously explored noncommuting groups, namely the group M 16 (Mihalkovich, 2018;Mihalkovich et al, 2020). We define this general form in the next section and present some important facts useful for our goals.…”
Section: Our Contributionsmentioning
confidence: 99%
“…The proof of this fact in the special case of M 16 was presented in Mihalkovich (2018). Since the idea of the proof remains the same, we omit it to shorten the paper.…”
Section: Mathematical Backgroundmentioning
confidence: 99%